Polypropylene-based Multilayer Plastic Waste Utilization on Bitumen Modification for Hot-Mixed Asphalt Application: Preliminary Study - Nugraha, Adam F.; Naindraputra, Ardhito J.; Gaol, Calvin S. A. L.; Ismojo, Ismojo; Chalid, M. (Journal of Applied Science, Engineering, Technology, and Education, 2022)
Plastic waste that has not been appropriately managed has caused concern for various stakeholders and has a negative impact on the environment. A way to minimize this issue is by promoting a circular economy through recycling. Despite this, many plastic wastes cannot be economically recycled; one of them is multilayer plastics due to the difficulty in sorting out the various types of materials contained in the layers. As an alternative, it may be possible to utilize multilayer plastic as a bitumen mixture; this method may avoid the separation process entirely. Bitumen is a component of asphalt, which is crucial to the construction of infrastructure. Plastics can potentially enhance the properties of modified bitumen, and they would assist in enhancing the quality of the asphalt. The aim of this study is to examine the impact of multilayer waste plastics on bitumen fabricated by the hot-mixing process. To enhance the compatibility between hydrophobic plastic and hydrophilic bitumen, lignin was used as a compatibilizer. The properties of bitumen with 3, 4, and 5 wt.% multilayer plastic and mixing times of 15, 30, and 45 minutes were evaluated. Accordingly, surface, chemical, thermal properties, and morphology were evaluated using sessile drop tests, Fourier Transform Infrared, thermogravimetry analysis, and scanning electron microscopy.